West Point, Bataan and beyond : Santiago Guevara and the war in the Philippines - Guevara, Nick J. (Silver Spring, MD : Garfield Street Publishing, 2016)
A remarkable life! As a poor teenager in the Philippines, Santiago Guevara won a coveted appointment to the U.S. Military Academy at West Point. This ordinary man, thrust into extraordinary circumstances, would later walk and fight alongside generals and presidents. West Point, Bataan and Beyond is a narrative of World War II in the Philippines, seen from the unique perspective of a peacetime Filipino-born U.S. Army officer. One December morning in 1941, life as he knew it changed forever. It is a story of success and fulfillment, of defeat and despair, of hope and ultimate survival. - from the back cover
Lolo and Nona -- Empire and the Philippine islands -- Benevolent paternalism -- Honors, West Point and infantry -- The pearl of the orient -- The Philippine scouts and racial politics -- Marriage and family -- Baguio and the Philippine Military Academy -- "A treacherous people" -- Flight from Baguio -- First combat action to first regular division -- The battle in Bataan -- Abandoned, sick, and starving -- The death march -- "Andersonville of the Pacific" -- "Tchaikovsky to my ears" -- Camp visits and guava details -- Care packages and Cochero news -- Parole, the Resistance and the Makapili -- Life under occupation -- The Manila massacre -- War crimes tribunal -- A choice and a new home -- Further adventures -- Oldest graduate, oldest scout -- Martyrs, heroes, survivors -- Afterword by Carmen Guevarra Neuberger -- Appreciation -- Appendix A: Filipino West Point Cadets 1914-1941 -- Appendix B: POW letters -- Appendix C: Documents -- Selected bibliography -- Biographical index
With bibliography and index
English
Keywords: Guevara, Santiago; Filipino soldiers -- Biography; World War, 1939-1945 -- Prisoners and prisons -- Philippines